ANALISIS IMPLEMENTASI STRATEGI CONTENT MARKETING DALAM MENINGKATKAN CUSTOMER ENGAGEMENT (Studi pada Strategi Content Marketing Amstirdam Coffee Malang) - Fachrizal Abiyyuansyah; Andriani Kusumawati; Ari Irawan (Fakultas Ilmu Administrasi Universitas Brawijaya, 2019)
This research possesses a background on marketing development especially in Digital Marketing. This research have a purpose to: (1) Discover and define the implementation of Content Marketing Strategy Amstirdam Coffee Malang, (2) Discover and define the form of Customer Engagement based on the implementation of Content Marketing Strategy Amstirdam Coffee Malang, (3) Discover and define the effect of the implementation of Content Marketing Strategy on Customer Engagement Amstirdam Coffee Malang. The research method is using qualitative research. The data collection is using semi-structured interview, participative observation, and documentation. The informant of this research has an amount of ten informant. The research validity is using triangulation technique. The data analysis is using Miles and Huberman data analysis model. The result of this research is the implementation of Content Marketing Strategy Amstirdam Coffee Malang is corresponding with the channel of Content Marketing according to the experts. Content Marketing Amstirdam Coffee Malang is capable to form Customer Engagement dimension that is Affective Engagement, Cognitive Engagement, and Behaviour Engagement. The effect of the implementation of Content Marketing Amstirdam Coffee Malang is able to increase Customer Engagement which is measured using Customer Engagement Value. Keywords: Digital Marketing, Content Marketing, Customer Engagement, Customer Engagement Value. АBSTRАK Penelitian ini memiliki latar belakang berupa perkembangan pemasaran terutama pada Digital Marketing. Penelitian ini bertujuan untuk: (1) Mengetahui dan menjelaskan implementasi strategi Content Marketing Amstirdam Coffee Malang, (2) Mengetahui dan menjelaskan bentuk Customer Engagement berdasarkan implementasi strategi Content Marketing Amstirdam Coffee Malang, (3) Mengetahui dan menjelaskan dampak implementasi strategi Content Marketing terhadap Customer Engagement Amstirdam Coffee Malang. Metode penelitian yang digunakan adalah penelitian kualitatif. Pengumpulan data menggunakan wawancara semi-terstruktur, observasi partisipatif, dan dokumentasi. Informan dari penelitian ini berjumlah sepuluh informan. Validitas penelitian menggunakan triangulasi teknik. Analisis data menggunakan model analisis data Miles dan Huberman. Hasil dari penelitian ini adalah implementasi strategi Content Marketing Amstirdam Coffee Malang sudah sesuai dengan alur Content Marketing menurut para ahli. Content Marketing Amstirdam Coffee Malang mampu untuk membentuk dimensi Customer Engagement yaitu Keterlibatan Afektif, Keterlibatan Kognitif, dan Keterlibatan Perilaku. Dampak implementasi Content Marketing Amstirdam Coffee Malang dapat meningkatkan Customer Engagement yang diukur menggunakan Customer Engagement Value. Kаtа Kunci: Digital Marketing, Content Marketing, Customer Engagement, Customer Engagement Value.